(untitled) (Research, Society and Development, 2023)
Schoolchildren are a group with a greater propensity to be exposed to contaminated environments, which favors the involvement of pathologies caused by geo-helminths. Therefore, this study aims to determine the clinical and socioeconomic changes associated with infection by parasitic diseases in children. This is a cross-sectional observational study to verify the clinical, parasitological and socioeconomic alterations of children seen at the pediatrics of the Nosso Lar community, located in the Vergel do Lago neighborhood, Maceió-AL. It was found among the samples of biological material that 20.4% were positive for gastrointestinal helminths, of which 66.7% were positive for Ascaris lumbricoides, 22.2% for Ancylostoma duodenale and 11.1% for Hymenolepis diminuta, as well as it was found that 39% of children drink tap water, 42.8% do not have the habit of washing their hands before meals and more than half do not have basic sanitation in their homes. It was also observed that most mothers had incomplete elementary school education and most had an income of up to one minimum wage. Thus, we conclude that the sanitation and hygiene conditions contributed to the number of positives. The prevalence of Ascaris lumbricoides suggests the low adherence to the habit of hand hygiene by the children. Most of them lived with about seven people and in rented houses, with low income, showing their precarious socioeconomic level. Moreover, the low level of education of the mothers predisposes to significant resistance to return with the stool sample.